A influência do tamanho de área protegida na composição e conservação de aves no Cerrado - Pereira, Caio Stuart Amorim (2011)
The Cerrado has a huge variety of ecosystems are able to offer resources and conditions for more than half of the birds found in Brazil. Its great extent and location on the continent favors contact with birds of different biomes. All this diversity of birds is threatened by processes that reduce natural cover your area. The selection of protected areas is aimed to represent the largest number of local species and their populations remain viable over time. This strategy is used from the predictions of the theory of island biogeography implies a positive relationship between the size of the area and its species richness. Other important elements of biodiversity may be absent only selected areas of the potential size of the area. In a protected area of the Cerrado conducted a field study in which we ascertain the status of endemism and threat to local bird community analyzed the influence of seasonality on the composition of its avifauna. In the second part of our work grouped the 12 species in protected areas in the Cerrado by their similarities in the use of resources in the environment. We tested the relationship between area size and species richness considering the variations in the composition of functional groups and number of endemic species and / or threatened. We discussed how big an area can influence the priorities for bird conservation in the biome. We found that the area has a strong influence on the number of species from one location. However, we point out some aspects that highlight a set of small areas in the conservation of bird diversity in Cerrado.